Aromatic liquid crystalline copolyesters with low Tm and high Tg: Synthesis, characterization, and properties. Issue 13 (6th February 2014) - Wei, Peng; Cakmak, Miko; Chen, Yuwei; Wang, Xinhang; Wang, Yanping; Wang, Yimin
ABSTRACT In this study, a series of aromatic copolyesters P‐BPAx with lower melting temperature and higher glass transition temperature derived from hydroxybenzoic acid (HBA), 6‐hydroxy‐2‐naphthoic acid (HNA), bisphenol A (BPA) and terephthalic acid (TA) were synthesized via melt polymerization. The copolyesters were characterized by FTIR, solid state 13C NMR, DSC, TGA, polarized optical microscopy, X‐ray diffraction, and rheometry measurements. With addition of BPA, the resulting copolyester's melting temperature decreased from 260 to 221°C and its glass transition temperature increased from 70 to 135°C, compared with the parent copolyester P‐HBA70 (HBA/HNA copolymer). With exception of copolyester P‐BPA5.0 (225–280°C), the copolyesters could maintain liquid crystalline behavior in a broad temperature range from 230°C to higher than 410°C. The ability to form nematic liquid crystalline phase disappeared when BPA concentration became higher than 15 mol %. X‐ray diffraction analysis showed crystallinity decreased as the BPA content increased. A slightly distorted O" and a substantially distorted O′ orthorhombic phase was observed for P‐BPA2.5. Upon annealing at 220°C, the O" phase disappeared and the O′ phase became stronger gradually. Rheology study data showed the ability to process the copolyesters improved in those compositions containing <2.5 mol % BPA. Continuing to increase concentrations of BPA, they became intractable. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40487.